Reframing Arabic Reading Pedagogy through Problem-Based Learning: An Intrinsic Case Study in Islamic Senior High School - Khoirotun Ni’mah; Muhammad Samsul Ulum; Abdul Wahab Rosyidi; Muhammad Yakut Bainal Hajar (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2026)
Background: Arabic reading instruction in Madrasah Aliyah is often dominated by literal and transmissive approaches, limiting students’ engagement and higher-order thinking.Objective: This study aims to analyze the implementation of Problem-Based Learning (PBL) in Arabic reading instruction, focusing on student engagement, learning processes, and contextual factors influencing its application.Method: Employing a qualitative approach with an intrinsic case study design, this research involved two Arabic teachers and 30 purposively selected tenth-grade students. Data were collected through participant observation, semi-structured interviews, and document analysis, and analyzed using reflexive thematic analysis.Results: The findings reveal that PBL transforms reading instruction into a dialogic and problem-oriented process through authentic text problematization and collaborative inquiry. This approach enhances students’ cognitive, emotional, and social engagement, particularly in developing inferential comprehension and critical interpretation of texts. Supporting factors include teachers’ pedagogical competence and a collaborative school culture, while challenges involve time constraints and diverse student abilities.Conclusion: This study contributes theoretically by extending constructivist reading pedagogy into the context of Arabic literacy in Islamic education, highlighting how PBL facilitates meaning-making through socio-religious texts. Practically, it offers an implementable framework for designing contextual and dialogic Arabic reading instruction that promotes critical literacy. These findings provide new insights into how and why PBL works in complex linguistic and cultural learning environments.